Labour migration and its impact on non-capitalist social formations : a comparative study of the Tonga and Ngoni-Tumbuka in Malawi, circa 1880 to 1940 - Reeler, Douglas Andrew (School of Economics, 2023)
This thesis is a study of labour migration from Malawi, specifically an examination of the impact of immigrants on the non-capitalist social formations of the Tonga and Ngoni-Tumbuka under colonial-capitalism .until 194-0. It is an attempt to locate and analyse transformations of the major social. Relations which structured and organised the lives of the Tonga and Ngoni ... Turnbuka at the rural, ·village level during the period under review. An academic thesis of this nature has severe limits in that it cannot begin to grasp the day-to-day lived experience of those who were subjected to the. profiteering onslaught of colonial capitalism. · The separation of husbands from wives and children, this hunger and fear, the drudgery and humiliations and the brave . . ' Resistance and struggles of ordinary· people to maintain their self-dignity under conditions of increasing impoverishment do not emerge clearly from official colonial reports concerned with tax returns, law and order and economic development for Imperial expansion. Without a presentation and understanding of these experiences an analysis of this nature is necessarily incomplete. i This is not merely an ideological standpoint but one that recognises that social transformations are forged by people, day by day, reacting to conditions that confront their livelihood, their security ty and mental well-being. As such it is through these · lived experiences that historical change takes place . . The economic development of Malawi has taken place along three major lines. Under colonialism, the north of Malawi, where the Tonga and Ngoni-Tumbuka lived and still live, developed rapidly into a labour-reserve economy serving mines and farms all around the southern sub-continent. In the centre and south developed peasant cash-cropping with some labour-migration and a weak capitalist plantation economy. More recently, labour migration to neighbouring countries has been dramatically reduced and the labour redirected to peasant cash-cropping and to the capitalist plantation economy undergoing expansion in the central and northern regions. This has occurred under the direction of multinationals and a tiny national bureaucratic bourgeois class indistinguishable from the present regime. Labour migration thus remains a crucial phenomenon in the present development and underdevelopment of the Malawian economy. Although migration is now more internal than external it still bears the same characteristics, in that migrants have retained material links with non-capitalist economies where their families undertake subsistence agriculture for their own survival, thus enabling plantation owners to pay single men's wages. The political and social forms arising out of these relations are thus crucial in the make-up of the State and for the future trajectory of the economy. It is in the context of this that a historical study of the impact of labour migration on non-capitalist social formations in northern Malawi has relevance. Chapter One sets out a broad theoretical position within which the relationship between capitalist and non-capitalist modes of production can be analysed. This is argued in terms of the debate between those who opt for seeing a social formation as an articulation of constituent modes of production and those · who see a social .formation as ._containing one mode of production. The former position is seen here as the most useful. Chapter Two theoretically defines and elaborates on wh.at I have - called the domestic non-capitalist mode of production. 'This sets out the theoretical basis for my analyses rn Chapter Three and Four of the Ngoni-Tumbuka and Tonga domestic modes of production and social formations. This chapter looks at the relations and forces of production in terms of the agricultural cycle, relations of exploitation between elders and juniors and marriage organisation. Chapter Three gives a concrete analysis of the Tonga social formation before colonialism, in order to locate major social relations later transformed under colonial-capitalism and the impact of labour migrancy studied in Chapter 7 . As such it concretises relations posited in Chapter 2. Chapter Four gives a similar analysis to Chapter Three, studying the Ngoni-Tumbuka social formation before colonialism as a pre-- cursor to Chapter Eight.· Chapter Five sets out some theoretical arguments on the nature of labour migration. The first. Part locates the available surplus labour-time in domestic economies. The second part looks at the appropriation of this surplus labour-time and the nature of exploitation of domestic producers under the system of migrant labour in terms of the reproduction of migrant .labour- . power by migrants' families. Lastly the various concrete forms of labour migration in colonial Malawi are examined. Chapter Six begins with some theoretical observations on the Colonial State and the nature of Imperialist intervention in Africa in the late· 1800 s. This is followed by a schematic analysis of the Colonial State formation in Malawi from 1890 to 1940 in terms of the development of labour migration. Chapter Seven studies the impact of labour migration on the Tonga social formation until 1940. The first part gives background information on the patterns of labour migration from Tongaland. This is followed by an analysis of the. role of missionaries, after which is a study of the role of the Colonial State and the political struggles, at the level 0£ the. local state, involved in the transformation of Tonga social ~elations. The next section deals with the social processes of migrancy within Tonga villages until 1917. After this subsistence and market production relations from 1917 to 1940 are examined followed by a study of the processes of dispersal of homesteads consequent upon shifting power relations from elders to junior migrants. Finally, the re-organisation of marriage relations involved in the shifting of power relations is examined in greater depth. chapter Eight is a similar analysis to Chapter Seven, studying the case of the Ngoni-Tumbuka. The first three sections (patterns, missions, and local state) are similar in approach to the previous chapter. The fourth section studies the underdevelopment of the subsistence economy, followed by an examination of the transformations of relations linking the cattle economy to marriage organisation, with the development of labour migration. The chapter ends with a study of the dispersal of villages within the context of struggles between the Ngoni 'aristocracy' and Ngoni-Tumbuka commoners. Comparisons and contrasts between developments in the two social formations are given in Chapters Seven and Eight.